2021
DOI: 10.3389/fneur.2021.607907
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Patients With Auditory Processing Disorder in Getting Support in Health, Education, and Work Settings: Findings From an Online Survey

Abstract: Objective: To explore the views and experiences of individuals with Auditory Processing Disorder (APD) and/or their families in getting support from services and to receive their suggestions for improvement.Design: Cross-sectional random sample survey with descriptive analysis.Settings: Online survey.Participants: One hundred and fifty six individuals with APD and/or their family members from the APD Support UK patient support organization and four associated APD Facebook groups.Main Outcome Measure: A 16-item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Recent figures obtained following Freedom of Information requests by the APD Society UK found that only 54% of English and Welsh local authorities actually have an APD policy (128). This is consistent with empirical evidence showing that individuals themselves, and the families of individuals with APD, overwhelmingly report difficulties in getting access to diagnosis and support, and a lack of awareness of APD across health and education (129).…”
Section: Discussionsupporting
confidence: 86%
“…Recent figures obtained following Freedom of Information requests by the APD Society UK found that only 54% of English and Welsh local authorities actually have an APD policy (128). This is consistent with empirical evidence showing that individuals themselves, and the families of individuals with APD, overwhelmingly report difficulties in getting access to diagnosis and support, and a lack of awareness of APD across health and education (129).…”
Section: Discussionsupporting
confidence: 86%
“…APD is a rare disorder and clinics typically receive few APD referrals per year. It has also been reported that obtaining a referral for APD diagnosis is difficult (Moore et al, 2018;Agrawal et al, 2021). For these reasons, there was a limited amount of data available for this study and it took approximately six years to collect the data within the dataset.…”
Section: Data Augmentation Techniquesmentioning
confidence: 99%